Special traits of the millimeter wave relativistic magnetron - Berdin, S.A.; Chizhov, K.V.; Gadetski, N.P.; Korenev, V.G.; Lebedenko, A.N.; Marchenko, M.I.; Magda, I.I.; Melezhik, O.G.; Sinitsin, V.G.; Soshenko, V.A. (Вопросы атомной науки и техники, 2014)
A 8 mm band relativistic magnetron is investigated experimentally and by means of numerical simulation. The physical effects are analyzed which influence negatively the r.f. generation. The processes capable of reducing effectiveness of the generation and duration of the generated pulse include forward and backward axial flows of electrons, and intense electric fields – the generated microwaves and the fields owing to the space charge.